PENERAPAN MODEL PEMBELAJARAN AKTIF, KREATIF, EFEKTIF DAN MENYENANGKAN (PAKEM) TERHADAP HASIL BELAJAR SHOOTING BOLA BASKET (STUDI PADA SISWA KELAS IX SMP NEGERI MODEL TERPADU BOJONEGORO) - ANGGARA P, FITRIAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Physical education is needed in schools, since physical education in an important part of human development to achieve the overall adicational. Physical education does not only improve physical fitness, but also it provides varieties and meaningful movements for children. Based on several observations, basic techniques learning of volleyball under passing had less interaction between teachers and students. Students tend to be passive in learning activity, especially for volleyball under passing material which affected declining of students’ achievement through learning process. This case was because the learning model used by the teacher was not appropriate to increase students' abilities. Then the researchers gave the model PAKEM as learning models have noticed some of the characteristics of learning that is active, creative, effective and fun, in order to reach learning objectives with good and satisfy learning achievement. Statement of problems in this study was to determine: (1) Is there any effect to the application of Active Learning Model towards learning achievement of volleyball under passing at SMAN 1 Singgahan? (2) How big the influence of Active Learning Model implementation towards learning achievement of volleyball under passing at SMAN 1 Singgahan?. The object of study was students of 10th grade of Senior High School 1 Singgahan Tuban with the number of samples taken 2 classes, that class X-2 by the number of 33 students as the experimental group, and class X-4 by the number of 34 student as a control group. The method in this analysis used descriptive quantitative statistical methods. Conclusions in the study were: (1) There was a significant effect in learning achievement of volleyball down passing after Active Learning Models application which was showed by t test, obtained the value (tcount 2,184 > ttable 1,668) with level of significance 0,05%. (2) The amount of influence on Learning achievement of volleyball under passing which amounted to 45,98%. Keywords: Learning Model, PAKEM, Basketball Shooting.